Learning curve in rat dissection for experimental sciatic nerve repair - Marin Andrei; Marin Georgiana Gabriela; Dobrete Nicoleta Amalia; Enescu Dan Mircea (Romanian Neurosurgery, 2019)
The baseline for any key research in nerve regeneration is an experimental model and the sciatic nerve in the rat model is the workhorse in this field. Although physically resistant to external traumas, a surgical intervention constitutes a major distress even for a rat. In the following presentation, we will analyse the learning curves for different stages in the rat sciatic nerve surgery as well as possible factors which influence these times.